DB2® Version 8: The Official Guide - Zikopoulos, Paul C. (Prentice Hall PTR, 2011)
IBM DB2 Universal Database v8.1.2 will help you access any information, from any application, from anywhere in your organization, anytime—and do it all more easily and cost-effectively than you ever thought possible.